From the 'Aesthetics of Diversity' to the 'Poetics of Relating': Segalen, Glissant and the Genealogies of Francophone Postcolonial Thought. Issue 2 (July 2014) - Forsdick, Charles
<x xml:space="preserve">Abstract</x> The article explores the 'significant missed rendezvous' and posthumous critical dialogue between Victor Segalen (1878–1919) and Édouard Glissant (1928–2011). It studies the ways in which the Martinican novelist, poet and theorist identified Segalen as a catalytic presence in his thought and as one of his privileged, lifelong interlocutors. The study tracks the role of Segalen's work in the steady emergence and elaboration of Glissant's thought, but also analyses the place of Glissant's readings in the progressive reassessment of Segalen's own writings (and particularly in their recent recontextualization in a postcolonial frame). The article contributes to reflections on the formation of communities of thought in which intellectuals from different moments and different ideological niches — in this case colonial and postcolonial — are drawn into dialogue in ways that appear achronological. Segalen and Glissant are presented as part of a wider community of French-language writers, linked with 'relational' ties, whose engagements with questions of contact and cultural diversity overlap, intersect and ultimately interact.